If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + t = 7 + -55 Combine like terms: 7 + -55 = -48 Y + t = -48 Solving Y + t = -48 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-1t' to each side of the equation. Y + t + -1t = -48 + -1t Combine like terms: t + -1t = 0 Y + 0 = -48 + -1t Y = -48 + -1t Simplifying Y = -48 + -1t
| 4u+8=0 | | -18-k=37 | | -10-(48Q)+(15Q^2)-(Q^3)= | | 9+3w=8+9w | | 229=5-14x | | -10+110x=10x-110 | | 6-x=30 | | 6x+67=2080 | | -1=6+x | | (15x-43)+(8x+18)=90 | | 11+6-x=52 | | 12x-11x=3x+24x-80 | | a/5-4=-6 | | (7/x)+(1/2)=(8/x) | | 0=-8w+20 | | -66p+48-8p-12=3p-4p | | -16=c-22 | | -45=d-50 | | 25000-2x=0 | | 4=y-16 | | -3(3y-6)+2(2y+7)= | | 3[x+2]=11 | | -7+y=-4 | | 7x-16-3x=6x-9 | | -8(y+4)=10y+5 | | 11-y=5 | | (x+3)(x-3)=(x+7)(x-8)+9 | | 13=38+x | | 7x-23=17-3x | | (6x+44)+(-10x+65)=117 | | -6(x-1)=3(3-2)x | | (4x^-1y^3/9x^3y)^3/2 |